2013
DOI: 10.1111/pcn.12005
|View full text |Cite
|
Sign up to set email alerts
|

Broader autistic phenotype in parents of children with autism: Autism Spectrum Quotient–Turkish version

Abstract: Aims:The Autism Spectrum Quotient (AQ) is a selfassessment screening instrument for measuring the degree to which an individual of normal intelligence shows autistic traits. Genetic factors could be responsible for the relatives of individuals with autism exhibiting higher than normal rates of autism-related impairments, referred to as the 'broader autism phenotype' (BAP). The aim of this study was to test whether there is a difference between the parents of autistic and those of typically developing children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…Family members of children diagnosed with ASD have been reported to display more autism spectrum traits, including social skills and communication impairments, than family members of normal controls [26,27]. Social deficiency in the relatives of people with ASD may therefore reflect the heritability of the underlying physiology important to social behaviors (i.e., OXT or AVP).…”
Section: Introductionmentioning
confidence: 99%
“…Family members of children diagnosed with ASD have been reported to display more autism spectrum traits, including social skills and communication impairments, than family members of normal controls [26,27]. Social deficiency in the relatives of people with ASD may therefore reflect the heritability of the underlying physiology important to social behaviors (i.e., OXT or AVP).…”
Section: Introductionmentioning
confidence: 99%
“…A total of ten reports measured the BAP using the self-report AQ (ES range: 0.01–1.34). Three studies used adaptations of the AQ: one in Italian [17], one in Turkish [18], and one in French [19]. Within the “social skills” factor, five studies found significantly higher deficits in social skills compared to parents of typically developing children [17, 18, 2022].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used adaptations of the AQ: one in Italian [17], one in Turkish [18], and one in French [19]. Within the “social skills” factor, five studies found significantly higher deficits in social skills compared to parents of typically developing children [17, 18, 2022]. Two studies reported significantly higher prevalence of “Attention Switching” deficits between the index parents and parents of typically developing children [22] and parents of children with specific language impairment [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it could be argued that whether parents have mentally disabled and autistic children also has an effect on their behavioral patterns. In some studies, it was found that the parents with autistic children have higher level of broad autism phenotype characteristics than the parents with normally developing children in the areas of social skills and communication (Bishop et al, 2004, Köse et al, 2013. It was also suggested that mild disorders in social communication especially affect the males (Skuse, Bruce, Dowdney and Mrazek, 2011).…”
Section: Introductionmentioning
confidence: 96%